El abordaje teórico y clínico de la orientación sexual en Psicología - Brizuela R., Armel (2012)
This paper reflects on how the cognitive, behavioral, and psychoanalytic have addressed the issue of sexual orientation. It sets out how the cognitive perspective has focused on the correlation between sexual orientation and some cognitive processes. It also reports how the psychoanalytic approach has rearranged by a critical review of their own theories, the status of homosexuality, which no longer posits that this is a pathological deviation, but a valid sexual option. Finally, it explains how the behavioral paradigm has emphasized the clinical setting, so that those who have chosen non-heterosexual orientations accept their choice and achieve successful integration.